Stochastic Modeling of Mouse Motor Activity under Deep Brain Stimulation: The Extraction of Arousal Information - Keenan, Daniel M.; Quinkert, Amy W.; Pfaff, Donald W. (PLOS Computational Biology, 2015)
Author Summary Brainstem and thalamic regulation of arousal has been studied experimentally since the mid 20-th century. Today, Deep Brain Stimulation (DBS) is used in the treatment of movement disorders, chronic pain, clinical depression, amongst others. At present, the proper choice of DBS parameters (frequency and strength of the electric stimulation), and how those parameters should be modified as conditions change, are not well understood. In this work, using motor activity as the observed response, a statistical framework is developed for such study, and a quantitative relationship between parameter values and response is established. Within this framework, a possible correlate of arousal, the rapid onset of spatial (two-dimensional) movement, is uncovered and also studied. One long-term hope for techniques such as DBS are that they could assist in the treatment of disorders of consciousness, by supplementing or replacing (e.g., in Traumatic Brain Injury) what should ordinarily be the appropriate endogenous stimulation.